Tindak Tutur Direktif Guru Dalam Pembelajaran Madrasah Diniyah di TPQ Asy Syukur Dusun Bunut Kidul Pakis Malang - Muhammad Azhar Fatoni; Muhammad Bisyrul; Lorena Rizki Fatimah; Rudad Ilaina Rohmah (Jurnal Pengabdian Masyarakat, 2024)
This study examines and aims to describe the form of teacher directive speech acts in madrasah diniyah learning. This study uses a pragmatic approach, namely the Yule perspective directive speech act theory. The research data is in the form of utterances by teachers at the madrasah diniyah of TPQ Asy Syukur, Dusun Bunut Kidul Pakis Malang, which contain directive meanings. Data collection techniques using observation and documentation techniques. Data analysis techniques include data reduction (data reduction), data presentation (data display) as well as drawing conclusions and verification (conclusion drawing/verification). Based on the results of data analysis, it is concluded as follows, first, the category of teacher directive speech acts in madrasah diniyah learning at TPQ Asy Syukur Dusun Bunut Kidul Pakis Malang includes directive speech acts of asking, directive speech acts of hope, directive speech acts of commands, directive speech acts of asking, and acts of directive speech asks. It is hoped that the two results of this research can be used as a reference in selecting and using directive speech acts in madrasah diniyah learning. Thus, communication between teachers and students is more interactive and meaningful.